2005
DOI: 10.1002/jclp.20126
|View full text |Cite
|
Sign up to set email alerts
|

Placebo psychotherapy: Synonym or oxymoron?

Abstract: Contrary to some recent claims, the placebo effect is real and in some cases very substantial. Placebo effects can be produced or enhanced by classical conditioning, but consistent with virtually all contemporary conditioning theories, these effects are generally mediated by expectancy. Expectancy can also produce placebo effects that are inconsistent with conditioning history. Although expectancy also plays an important role in psychotherapy outcome, the logic of placebo-controlled trials does not map well on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 45 publications
1
93
0
9
Order By: Relevance
“…Results revealed improvements in executive-function, working memory and affect recognition in the cognitive remediation condition. Follow-up studies have shown that these improvements in cognitive function are durable and accompanied by improved work outcomes (Bell et al, 2003;2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed improvements in executive-function, working memory and affect recognition in the cognitive remediation condition. Follow-up studies have shown that these improvements in cognitive function are durable and accompanied by improved work outcomes (Bell et al, 2003;2005).…”
Section: Introductionmentioning
confidence: 99%
“…One well-accepted method for understanding the mechanisms of behavioral treatment effects is the "dismantling" or "component-control" design (e.g., Kirsch, 2005) in which elements of a complete therapy are first identified and then contrasted with a therapy that contains a subset of most, but not all of the elements of the complete therapy. This approach has been used effectively for understanding the elements of behavioral therapy crucial for improvement in anxiety disorders (Butler et al, 1991) and allows for specific causal inferences regarding a unique component of treatment that are not possible in the wait-list, or comparative control designs that have characterized many studies in this research domain to date (but see Medalia et al, 2000; for an exception).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the components that are considered active or specific would be considered characteristic, because typically they are deduced from psychological theories, which describe how they will improve the symptoms of a particular disorder. In contrast to the concept of specificity, which has been related to uniqueness of treatment components [18], components may be considered characteristic even though they may not be a unique component of a particular treatment package. All other factors that may contribute to a treatment effect but which have not (yet) been specified within a psychological theory would be considered incidental, no matter whether they are common to all treatments, shared by some or not at all related to the treatment itself, but, for instance, rather to the patient, therapist or to the conduct of the study.…”
Section: What Is Characteristic In Ptsd Treatments?mentioning
confidence: 99%
“…Whereas the first type of components has typically been described as 'specific' or 'active' components in psychotherapy outcome research, for the second type of components a number of synonymously used terms occur in the literature, although they may have slightly different connotations [17,18]. Such terms include 'common,' 'general' or 'non-specific' factors or 'psychological placebos.'…”
Section: What Is Characteristic In Ptsd Treatments?mentioning
confidence: 99%
“…Red placebos seem to be more effective pain relievers than white, blue or green placebos. The magnitude of the placebo response varies as a function of the stated dose consumed (Kirsch 2005).…”
Section: Box 1 Some Uses Of the Word Placebomentioning
confidence: 99%